Multi‐faceted brain changes associated with proximity to dementia onset: The PREVENT‐Dementia study: Neuroimaging / multi‐modal comparisons. (7th December 2020) - Mak, Elijah; Dounavi, Maria‐Eleni; Low, Audrey; McKiernan, Elizabeth; Carter, Stephen F; Newton, Coco; Williams, Guy B; Ritchie, Karen; Wells, Katie; Sahin, Zeynep; Terrera, Graciela Muniz; Carriere, Isabelle; et al.
Abstract: Background: First‐degree relatives of people with dementia (FH+) are at increased risk of developing Alzheimer's disease (AD). Identifying preclinical brain changes would facilitate both early quantifiable longitudinal disease monitoring and interventional trials. However, the literature of imaging changes in FH+ remains highly controversial. We aim to investigate "estimated years to onset of dementia" (EYOD) as a surrogate marker of preclinical progression and assessed whether FH+ approaching the parental age of dementia onset would express more severe patterns of longitudinal brain changes. Method: 89 FH+ persons underwent serial 3T‐MRI with T1‐MPRAGE, DWI and ASL (mean interval: 2 years). The longitudinal Freesurfer pipeline was used to segment hippocampal subfields and early‐AD regions. Partial‐volume corrected ASL data and DWI data were processed with FSL‐BASIL4 and DTI‐TK5. Small vessel disease was indexed with white matter hyperintensities (WMHs) (Figure 1). We applied linear mixed effects models to predict MRI changes relative to EYOD, accounting for age, gender, education and time from baseline. Secondary analyses examined the interaction of APOE‐ε4+ on proximity‐related brain changes. Result: A shorter EYOD was associated with progressive decrease in FA, increase in MD/RD and atrophy of the fusiform gyrus over time (Figure 2). Interaction analyses revealed that APOE‐ε4+ carriers showed significant longitudinal atrophy of the hippocampal subfields with shorter EYOD. In contrast, cortical perfusion increased before plateauing ∼10 years before estimated onset. There were no associations of EYOD with mean cortical thickness or WMHs (See Figure 3 for a summary of main findings). Conclusion: Our findings represent the first extensive characterisation of longitudinal brain changes associated with proximity to dementia in FH+. Individuals who are approaching their parental age of dementia onset may be showing incipient brain abnormalities, particularly amongst APOE‐ε4 carriers. The specificity our findings in early‐AD regions also confer support to biological validity of EYOD as a stage marker of preclinical progression. Further ongoing clinical follow‐up of our sample would provide critical validation of these findings.